Resolving the Capability–Rigidity Paradox in New Product Innovation - Atuahene-Gima, Kwaku (Journal of Marketing, 2005)
Managers face an important strategic dilemma in product innovation: how to exploit existing product innovation competencies (competence exploitation) while avoiding their dysfunctional rigidity effects by renewing and replacing them with entirely new competencies (competence exploration). Although the resolution of what is termed the “capability–rigidity paradox” is considered a fundamental managerial task in enhancing product innovation outcomes and the firm's competitive advantage, it has received little research attention. The author argues and finds support that market orientation provides a key to this paradox. Specifically, customer and competitor orientations ensure simultaneous investments in exploiting existing product innovation competencies and exploring new ones. The author also finds that the effects of these orientations on competence exploitation and exploration are differentially moderated by interfunctional coordination and perceived market opportunity. Regarding outcomes, competence exploitation and exploration have opposing relationships with incremental and radical innovation performance. However, the relationship between competence exploration and radical innovation performance is positively moderated by interfunctional coordination. Overall, the results of this study suggest that market orientation can prevent a firm from becoming operationally efficient but strategically inefficient by simultaneously engendering competence exploitation and exploration, which are differentially related to incremental and radical product innovation outcomes.